Análisis de cartera vencida y propuesta de minimización de riesgos crediticios en la cooperativa de ahorro y crédito nuevo Ambato LTDA. sucursal Machachi del cantón Mejía provincia de Pichincha en el período 2014 - Gualpa Gualpa, Víctor Alfonso (2015)
This researching contributes to strategies to minimize credit risk in the Credit Union New Ambato Ltda., Branch Machachi, canton on a thorough analysis of the risks to which the institution has not given due importance. The main weakness of the cooperative was the challenge posed to managers, controlling and minimizing credit risks, by implementing policies that has not been fulfilling since comprehensive risk management, becomes a fundamental part strategy and key success factor and turn adds value in confidence and economic security for all who make up the cooperative especially for its customers and it is essential that the cooperative control have the tools to identify the activities, processes and the most important products of the company, as well as the type and level of risks that have caused more trouble determining them both external and internal factors that initiate credit risks. Because the cooperative is in a purely agricultural and livestock place it is essential to control the destiny of credits to thereby ensure the return of the same. The 5 S applied by the institution only them has allowed us to analyze, evaluate and process the l credit application shaping itself as requirements to submit to credit approval but does not guarantee that the partner meets the obligation acquired by what is to implement a sixth C, It is the control and monitoring where the fate of credit in this way will avoid the diversion check it.